On the “Perceptible Bodies” at De Generatione et Corruptione II.1 - Crowley, Timothy J. (Revista Archai, 2019)
Near the beginning of De Gen. et Cor. II.1, Aristotle claims that the generation and corruption of all naturally constituted substances are “not without the perceptible bodies” (328b32-33). It is not clear what he intends by this. In this paper I offer a new interpretation of this assertion. I argue that the assumption behind the usual reading, namely, that these “perceptible bodies” ought to be distinguished from the naturally constituted substances, is flawed, and that the assertion is best understood as a claim that Aristotle has established in the second half of the first book of the De Gen. et Cor.